PELATIHAN PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI DALAM UPAYA MENINGKATKAN LITERASI DIGITAL - Wae, Veronika P S M; Priska, Melania; Wao, Yosephina Payu; Jariyah, Ainun; Dhone, Maria Tifana (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The community service to society activity (CSS) in the form of training in the use of technology-based interactive learning media, namely Quizizz, aims to enhance the digital literacy skills of the Sare Pawe teacher-friendly community at SMPN 2 South Ende. The activities, conducted in the form of workshops, were attended by teachers and students, as well as lecturers and students from the Biology Education study program at the University of Flores, who served as resource persons. The training methods used were briefing, discussion, question and answer, and direct practice accompanied by mentoring. Based on the results obtained, it is known that the Quizizz platform is useful in efforts to improve digital literacy skills and abilities for teachers at SMPN2 South Ende. The Quizizz platform allows the creation of a learning process in the classroom by teachers more interactively and interestingly because of the gamification element, so that students become more enthusiastic about learning, which will have an impact on student learning outcomes.